Analisis Green Manufacturing Guna Meningkatkan Sustainability pada PT. XYZ Menggunakan Metode Life Cycle Assessment - Rahayu, Utari; W, Endang Pudji (Ekonomis: Journal of Economics and Business, 2025)
This study aims to measure the eco cost and determine the environmental impact of the CPO (Crude Palm Oil) production process and find suggestions for green manufacturing improvements in the CPO production process at PT XYZ. The research method used is the life cycle assessment (LCA) method through 4 (four) stages, namely: goal and scope definition; life cycle inventory; life cycle impact assessment; and interpretation. Furthermore, eco efficiency calculations are carried out to produce an eco cost value. The results of the study showed that the eco cost value of PT XYZ was Rp. 1,997,127. The potential impacts found were acidification, eutrophication, global warming, human toxicity, and photochemical oxidation. Global Warming is the biggest impact resulting from the CPO production process, which is 5.22 × 10^(-11) kg CO2 eq. With the use of diesel fuel as the most impactful material unit. Therefore, the proposed improvements given are utilizing empty fruit bunches and POME liquid waste as fuel and renewable energy and implementing a co-firing system to reduce emissions resulting from the CPO production process.